Semiconstrained Distal Radioulnar Joint Prosthesis - Savvidou, Christiana; Murphy, Erin; Mailhot, Emilie; Jacob, Shushan; Scheker, Luis R. (Journal of Wrist Surgery, 2013)
Distal radioulnar joint (DRUJ) problems can occur as a result of joint instability, abutment, or incongruity. The DRUJ is a weight-bearing joint; the ulnar head is frequently excised either totally or partially, and in some cases it is fused, because of degenerative, rheumatoid, or posttraumatic arthritis. Articles about these procedures report the ability to pronate and supinate, but they rarely discuss grip strength, and even less do they address lifting capacity. We report the long term results of the first 35 patients who underwent total DRUJ arthroplasty with the Aptis DRUJ prosthesis after 5 years follow-up. Surgical indications were all causes of dysfunctional DRUJ (degenerative, posttraumatic, autoimmune, congenital). We recorded data for patient demographics, range of motion (ROM), strength, and lifting capacity of the operated and of the nonoperated extremity. Pain and functional assessments were also recorded. The Aptis DRUJ prosthesis, a bipolar self-stabilizing DRUJ endoprosthesis that restores forearm function, consists of a semiconstained and modular implant designed to replace the function of the ulnar head, the sigmoid notch of the radius, and the triangular fibrocartilage ligaments. The surgical technique is presented in detail. The majority of the patients regained adequate ROM and improved their strength and lifting capacity to the operated side. Pain and activities of daily living were improved. Twelve patients experienced complications, most commonly being extensor carpi ulnaris (ECU) tendinitis, ectopic bone formation, bone resorption with stem loosening, low-grade infection, and need for ball replacement. The Aptis total DRUJ replacement prosthesis is an alternative to salvage procedures that enables a full range of motion as well as the ability to grip and lift weights encountered in daily living activities.
Keywords: distal radioulnar joint; wrist prosthesis; wrist arthritis